2017
DOI: 10.1080/14772019.2017.1312578
|View full text |Cite
|
Sign up to set email alerts
|

Vetigastropoda and Neritimorpha from the Lower Bajocian of Luxembourg and palaeobiogeography of Aalenian–Bajocian (Middle Jurassic) gastropods of western Europe

Abstract: Vetigastropod and neritimorph species from Lower Bajocian (Middle Jurassic) sediments of south-western Luxembourg are described. Eighteen species are recognized. Two new genera – Szabotomaria gen. nov. and Fabercapulus gen. nov. – and four new species – Szabotomaria ziqquratiformis sp. nov., Colpomphalus thuyi sp. nov., Colpomphalus tigratus sp. nov. and Fabercapulus semisculptus sp. nov. – are erected. These species, together with other species recently described from the same strata, are part of a diverse as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…For this reason, they substituted the family name Ataphridae with Collonidae. However, Monari et al (2018) maintained that this view is not justified. According to these authors, although the holotype is imperfectly preserved, it shows all the characters indicated in the original diagnosis and the uncertainty about its origin does not affect the availability of the taxon.…”
Section: Remarks According Tomentioning
confidence: 99%
“…For this reason, they substituted the family name Ataphridae with Collonidae. However, Monari et al (2018) maintained that this view is not justified. According to these authors, although the holotype is imperfectly preserved, it shows all the characters indicated in the original diagnosis and the uncertainty about its origin does not affect the availability of the taxon.…”
Section: Remarks According Tomentioning
confidence: 99%
“…He also tentatively classified most of the specimens of the other groups (Wendt 1971). The Trochoidea, Turbinoidea and supposed Rissooidea were treated in subsequent papers concerning the systematics of the gastropods at higher taxonomic rank (Conti et al 1993;Szabó et al 1993;Monari et al 1996). Conti et al (2004) reported a synthesis of the knowledge acquired so far in the study of these faunas.…”
Section: The Gastropod Faunasmentioning
confidence: 99%
“…The illustration of the type species (Das 2002, p. 104, text-figs 3, 4A-B) shows a very poorly preserved material which prevents more detailed comparisons. Pleurotomaria Defrance, 1826 has a more gradate shell and flatter base, the shoulder of the adult shell is provided with a row of nodes and the selenizone runs on the outer face (Monari & Gatto 2013).…”
Section: The Gastropod Faunasmentioning
confidence: 99%
See 2 more Smart Citations